As formas assumidas pelo trabalho : da cooperação simples ao toyotismo. - Gois, Patricia Monteiro de (2008)
The work while producing activity of values of use occupies a central place in the Marx´s thought. According to this philosophical chain, the work is the ontological and that it establishes category of the world of the men, therefore, is through the work that it happens the transformation of the nature in indispensable values to the material reproduction of the society, being, therefore, the perpetual natural condition of the life human being . However, in the continuation of the historical process, the perpetual condition of the existence human being assumes diverse forms. In this direction, this master´s thesis has as objective to verify, in accordance with the marxist theory, the process of evolution of the category work, specifically, in the capitalist production. For in such a way, it is looked to understand how it happens the extration of the productive excess, its evolution and improvement by means of the diverse forms of submission of the work to the capital - since the initial forms of production of merchandises until the systems contemporaries of extration of surplus-value. From now on it is demonstrated that, although the productive transformations in course, the work is the fundante category of the social being. The conclusion is that in the capitalism, the forms changes, but the content remains the same, it wants to say, the production and the accomplishment of surplus-value.